The genus Porana (Convolvulaceae) - A phytochemical and pharmacological review - Peng, Yu; Li, Ye; Yang, Yuanyuan; Gao, Yuanqing; Ren, Hui; Hu, Jing; Cui, Xiaomin; Lu, Wenjing; Tao, Hongxun; Chen, Zhiyong (Frontiers in Pharmacology, 2022)
There are about 20 species of Porana Burm. f. worldwide in tropical and subtropical Asia, Africa and neighboring islands, Oceania, and the Americas. In China, India, and other places, this genus enjoys a wealth of experience in folk applications. Nevertheless, the chemical composition of only five species has been reported, and 59 compounds have been isolated and identified, including steroids, coumarins, flavonoids, quinic acid derivatives, and amides. Pharmacological studies revealed that extracts from this genus and their bioactive components exhibit anti-inflammatory, analgesic, antioxidant, anti-gout, anti-cancer, and anti-diabetic effects. Although this genus is abundant, the development of its pharmacological applications remains limited. This review will systematically summarize the traditional and current uses, chemical compositions, and pharmacological activities of various Porana species. Network analysis was introduced to compare and confirm its output with current research progress to explore the potential targets and pathways of chemical components in this genus. We hope to increase understanding of this genus’s medicinal value and suggest directions for rational medicinal development.